THE EFFECT OF LIQUIDITY, SOLVENCY, PROFITABILITY, AND MANAGEMENT PLAN ON GOING CONCERN AUDIT OPINION (EMPIRICAL STUDY OF MANUFACTURING COMPANIES ON THE IDX LIST) - Christian Lie; Rr. Puruwita Wardani; Toto Warsoko Pikir (Berkala Akuntansi dan Keuangan Indonesia, 2016)
The auditor is in charge of assessing the fairness of the financial statements. In addition to getting information about the fairness of financial statements, users can also find out information about the company's ability to maintain its business continuity, namely through going concern audit opinions. The purpose of this study is to analyze the effect of liquidity, solvency, profitability and management plans on the acceptance of going concern audit opinions. The objects of this research are manufacturing companies listed on the Indonesia Stock Exchange from 2010-2012. The sample was selected by purposive sampling method. By using logistic regression analysis, the result is solvency and management plan have an effect on acceptance of going concern audit opinion, while liquidity and profitability have no effect on acceptance of going concern audit opinion.